Hamacher Operations on Picture Fuzzy Matrices - Ramakrishnan, M.; Sriram, S. (Communications in Mathematics and Applications, 2023)
In this article, Hamacher operations of Picture Fuzzy Matrices are proposed, which are direct extensions of Hamacher operations of Intuitionistic Fuzzy Matrices. By using these operations scalar multiplication and exponentiation operations are constructed for a picture fuzzy matrix and certain new relations are established
Keywords: Fuzzy matrix; Intuitionistic fuzzy matrix; Picture fuzzy matrix; Hamacher sum and Hamacher product